To Compare and Evaluate the Efficacy of 1% Alendronate Gel and 10% Doxycycline Gel as an Adjunct to SRP in Patients with Chronic Periodontitis: A Randomized Controlled Clinical Trial - Laloo Phassang; Radhika Kapoor; Prashant Tyagi; Amit Wadhawan (Journal of Pharmacy and Bioallied Sciences)
Background: Modern medicine has advanced drug delivery strategies for improved treatment outcomes with minimal systemic side effects. Local drug delivery is a promising approach, targeting therapeutic agents to specific tissues or organs, optimizing efficacy by concentrating medications at the site of action. This method offers advantages over systemic delivery, such as reduced dosage and frequency, minimized systemic toxicity, and the avoidance of gastrointestinal issues and first-pass metabolism. Researchers are continually seeking ways to enhance the safety and effectiveness of local drug delivery systems through new materials. Aim and Objectives: To evaluate and compare the clinical efficacy of 1% alendronate gel and 10% doxycycline gel when used as an adjunct to scaling and root planning in the treatment of patients with chronic periodontitis. Methodology: The study was conducted in Shree Bankey Bihari Dental College & Research Centre in Ghaziabad. In this randomized controlled trial, the impact of the local drug delivery agents on the pocket depths of 45 patients was assessed over six months. Changes in gingival index (GI), plaque index (PI), probing pocket depth (PPD), and relative attachment level (RAL) were measured across three groups: a control group (Group C) and two experimental groups (Group A and B). Acrylic stents were used to evaluate probing depth and attachment loss post-surgery, determining the relative attachment level. Results: At 3 and 6 months post-treatment, Group A showed superior results in gingival index, plaque index, probing depth, and relative attachment level compared to Group B. Both Groups A and B demonstrated significant improvements over Group C. A statistically significant difference was observed when comparing Groups A and B separately. Conclusion: The study found that both Group A and Group B showed better outcomes than Group C at the 3- and 6-month marks. A statistically significant difference was observed between Group A and Group B, with Group A (SRP + 1% alendronate gel) outperforming Group B (SRP + 10% doxycycline gel) in improving the periodontal index, sulcular depth, and relative attachment level.